4963 Kanroku: Asteroid with a possible precession of rotation axis. (April 2018) - Sokova, Iraida A.; Marchini, Alessandro; Franco, Lorenzo; Papini, Riccardo; Salvaggio, Fabio; Palmas, Teodora; Sokov, Eugene N.; Garlitz, Joe; Knight, Carl R.; Bretton, Marc
Abstract: Based on photometric observations of 4963 Kanroku as part of a campaign to measure its light-curve, changes of the light-curve profile have been detected. These changes are of a periodic nature, i.e. the profiles change with a detected period P = 16.4032 h. Based on simulations of the shape of the asteroid and using observational data, we make the assumption that such changes of the light-curve of the asteroid could be caused by the existence of a precession force acting on the axis of rotation of the asteroid. Simulations of the 4963 Kanroku light-curve, taking into account the detected precession, and the parameters for the shape of the asteroid, the modeled light-curves are in good agreement with the light-curves obtained from the observation campaign. Thus, the detected precession force may indicate a possible satellite of the asteroid 4963 Kanroku.